Android-Based Interactive Multimedia Development Using ISpring Suite 11 in Informatics Engineering Class X Senior High School - Martin, Rahmadini Triana; Syafril, Syafril; Yusri, Meldi Ade Kurnia; J, Fetri Yeni (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
This research focuses on developing interactive multimedia based on the Android platform for the eyes Information Technology lessons in class X high school (SMA). In an era marked by the growing role of technology in education, this research aims to create innovative and engaging learning tools that fit the curriculum while leveraging the capabilities of Android devices. This research followed a systematic development process, including needs analysis, design, development, implementation, and evaluation. This multimedia content combines various interactive elements such as quizzes, simulations, and multimedia presentations to improve students' understanding and retention of information technology concepts.This study also evaluates the usability, effectiveness and satisfaction of both students and teachers with the Android-based interactive multimedia that has been developed. The findings of this research indicate that the use of Android-based interactive multimedia has been proven to be highly valid in terms of validity and practicality testing. This Android-based interactive multimedia has proven to be very suitable, both in terms of its content, appearance, and how it is used in accordance with the needs and characteristics of students. This research ultimately aims to improve the quality of Information Technology education at the high school level through the use of innovative Android-based interactive multimedia.